THE USE OF NEUROLOGICAL IMPRESS METHOD (NIM) TO IMPROVE STUDENTS’ READING ABILITY AT THE EIGHT GRADE OF SMP TAMAN ASUHAN PEMATANGSIANTAR - Natanael Saragih; Bella Meylisawati Gultom (Program Studi Pendidikan Bahasa Inggris FKIP, 2019)
This research is focused in learning reading by using Neurological Impress Method (NIM) at SMP Swasta Taman Asuhan Pematangsiantar in the academic year 2019/2020. This study use pre-test, treatment, and post-test. By this research, it is hopes that it can be useful to improve reading ability with using Neurological Impress Method (NIM). The writer took 32 students in VIII-1 SMP Swasta Taman Asuhan Pematangsiantar as the sample of the research. The data were obtained by using pre-test and post-test, the pre-test was given of the students in VIII-1 before the treatment and the post-test was given after the treatment. To analyze the data and answer the problem, the writer used the theory from Arikunto Suharsimi. The data collection instrument is a multiple choice consisting of 10 items, and how to analyze it by following the correct answer based on the text and form each question the value 1. This research is focused on learning to read by using the Neurological Impress Method (NIM) at SMP Swasta Taman Asuhan Pematangsiantar in 2019/2020. This research uses pre-test, treatment, and post-test. With this research, it is expected to be useful to improve reading skills by using the Neurological Impress Method (NIM). The writer took 32 students in VIII-1 SMP Swasta Taman Asuhan as a research sample. Data were obtained using pre-test and post-test, pre-test was given to students in VIII-1 before treatment and post-test was given after treatment. To analyze data and answer problems, the authors use the theory of Arikunto Suharsimi. The data collection instrument was a multiple choice consisting of 10 items, and how to analyze it by following the correct answers based on the text and forming each question with a value of 1. From the results of the pre-test, an increase in students' abilities can be seen from the percentage of 71.87% and increased to 100% in the pot test, the mean score of the pre-test was 5.75 and increased to 8.75 in the post-test, standard deviation pre-test and post-test 1.75. From the results of data analysis the writer found that the facts using the Neurological Impress Method (NIM) students were better than before using the Neurological Impress Method (NIM), the results of the pre-test and post-test were significant influences in the use of the Neurological Impress Method (NIM) in the ability reading students in narrative text